2014
DOI: 10.1016/j.nbd.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the neurobiology of epilepsy: A preclinical perspective

Abstract: When all of the epilepsies are considered, sex differences are not always clear, despite the fact that many sex differences are known in the normal brain. Sex differences in epilepsy in laboratory animals are also unclear, although robust effects of sex on seizures have been reported, and numerous effects of gonadal steroids have been shown throughout the rodent brain. Here we discuss several reasons why sex differences in seizure susceptibility are unclear or are difficult to study. Examples of robust sex dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
115
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 113 publications
8
115
1
1
Order By: Relevance
“…In previous studies in female Wistar rats, we showed that the natural changes in sex hormone levels during the estrous cycle do not affect seizure susceptibility in the amygdala kindling model of TLE [48]. More recently, we reported that the stage of estrous cycle had no obvious effect on onset, duration, or severity of kainate-induced SE in female HL-SD rats [49], which is consistent with observations of Scharfman and MacLusky [47]. Furthermore, the estrous cycle did not affect susceptibility of HL-SD rats to pentylenetetrazole [49], confirming previous experiments of Finn and Gee [50] in SD rats.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In previous studies in female Wistar rats, we showed that the natural changes in sex hormone levels during the estrous cycle do not affect seizure susceptibility in the amygdala kindling model of TLE [48]. More recently, we reported that the stage of estrous cycle had no obvious effect on onset, duration, or severity of kainate-induced SE in female HL-SD rats [49], which is consistent with observations of Scharfman and MacLusky [47]. Furthermore, the estrous cycle did not affect susceptibility of HL-SD rats to pentylenetetrazole [49], confirming previous experiments of Finn and Gee [50] in SD rats.…”
Section: Discussionsupporting
confidence: 90%
“…Except in one rat, SE could be induced on the morning of estrus, although significantly higher doses of pilocarpine were needed compared with those needed during other stages of the estrous cycle. The situation might have been different had SE not have been induced always at the same time of the day in the morning (as in the study of Scharfman et al [31]) but at time of peak estradiol and progesterone levels during the 4-to 5-day estrous cycle of the rat [47]. However, our main interest was to determine whether the estrous cycle increases variability in individual responses to pilocarpine that may be involved in the substrain differences observed in the present and previous studies in female SD and Wistar rats [14,15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…By contrast, exposure to estradiol can suppress GABAergic inhibition of hippocampal neurons (Huang and Woolley, 2012). Consistent with these findings, estradiol can impact seizure susceptibility (Scharfman and MacLusky, 2014; Reddy, 2017). In addition, several studies have identified sex difference in mTOR signaling in non-CNS tissues and functions (Gürgen et al, 2013; Miller et al, 2014; Baar et al, 2016).…”
Section: Introductionsupporting
confidence: 70%
“…
CommentaryHormones influence neuronal excitability and seizure susceptibility in both adulthood and during development (1)(2)(3)(4)(5)(6)(7)(8). A paradigm illustrating these interactions is catamenial epilepsy, where seizures may cluster around specific periods of the menstrual cycle (3).
…”
mentioning
confidence: 99%